Fibroblast-Derived Extracellular Vesicles Induce Colorectal Cancer Progression by Transmitting Amphiregulin - Oszvald, Ádám; Szvicsek, Zsuzsanna; Pápai, Márton; Kelemen, Andrea; Varga, Zoltán; Tölgyes, Tamás; Dede, Kristóf; Bursics, Attila; Buzás, Edit I.; Wiener, Zoltán (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EV), structures surrounded by a biological membrane, transport biologically active molecules and represent a recently identified way of intercellular communication. Colorectal cancer (CRC), one of the most common cancer types in the Western countries, is composed of both tumor and stromal cells and the amount of stromal fibroblasts negatively correlates with patient survival. Here we show that normal colon fibroblasts (NCF) release EVs with a characteristic miRNA cargo profile when stimulated with TGFβ, one of the most important activating factors of fibroblasts, without a significant increase in the amount of secreted EVs. Importantly, fibroblast-derived EVs induce cell proliferation in epidermal growth factor (EGF)-dependent patient-derived organoids, one of the best current systems to model the intra-tumoral heterogeneity of human cancers. In contrast, fibroblast-derived EVs have no effect in 3D models where EGF is dispensible. This EV-induced cell proliferation did not depend on whether NCFs or cancer-associated fibroblasts were studied or on the pre-activation by TGFβ, suggesting that TGFβ-induced sorting of specific miRNAs into EVs does not play a major role in enhancing CRC proliferation. Mechanistically, we provide evidence that amphiregulin, transported by EVs, is a major factor in inducing CRC cell proliferation. We found that neutralization of EV-bound amphiregulin blocked the effects of the fibroblast-derived EVs. Collectively, our data suggest a novel mechanism for fibroblast-induced CRC cell proliferation, coupled to EV-associated amphiregulin.